1996
DOI: 10.1073/pnas.93.14.6970
|View full text |Cite
|
Sign up to set email alerts
|

Linker histones affect patterns of digestion of supercoiled plasmids by single-strand-specific nucleases.

Abstract: The effect of histone H1 binding on the cleavage of superhelical plasmids by single-strand-specific nucleases was investigated. Mapping of P1 cleavage sites in pBR322, achieved by EcoRI digestion after the original P1 attack, showed an intriguing phenomenon: preexisting susceptible sites became "protected," whereas some new sites appeared at high levels of H1. Similar results were obtained with another single-strand-specific nuclease, S1. Disappearance of cutting at preexisting sites and appearance of new site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We have shown above and previously that supercoiled DNA binds H1 much more strongly than does linear or relaxed circular DNA. Further, it has been established by two kinds of studies that binding of linker histones unwinds supercoiled DNA ( , ). If unwinding to a more weakly binding conformation is a consequence of binding, then that binding must be negatively cooperative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown above and previously that supercoiled DNA binds H1 much more strongly than does linear or relaxed circular DNA. Further, it has been established by two kinds of studies that binding of linker histones unwinds supercoiled DNA ( , ). If unwinding to a more weakly binding conformation is a consequence of binding, then that binding must be negatively cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been established by two kinds of studies that binding of linker histones unwinds supercoiled DNA (20,21). If unwinding to a more weakly binding conformation is a consequence of binding, then that binding must be negatively cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a preference of HI for four-way junction DNA (a structure present at the base of cruciforms in supercoiled plasmids) was previously reported from our laboratory (Varga-Weisz et al, 1993. However, such structures should be sensitive to cleavage by single-strand-specific nucleases such as SI or P1; no such cleavages occur in pBR322 at superhelical densities less negative than -0.03 (-13 superhelical turns) (Ivanchenko et al, 1996b;Carnevali et al, 1984). At the same time, the preferential binding of HI is still detectable, even at 1Io -0.012 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A reasonable corollary to this observation is that these proteins, in binding to superhelical DNA, might change the twist of the double helix and/or the writhing of the helical axis in space. Consistent with this notion, we have recently shown that titration of superhelical plasmid DNA with increasing amounts of histone H1 changes the patterns of cleavage by single strandspecific nucleases, causing disappearance of preexisting nuclease-sensitive sites at low and moderate H1 levels, followed by the appearance of new sites at high protein levels (4). A possible explanation for the disappearance of preexisting sites is that histone H1 binding absorbs some of the negative superhelical stress in the molecule (unwinds the DNA), so that the decreased stress leads to loss of stress-dependent sensitive sites.…”
mentioning
confidence: 52%